Computer simulation in initial teacher education: a bridge across the faculty/practice divide or simply a better viewing platform? - Lowe, Graham (2011)
This thesis reports on a mixed methods research project into the emerging area of computer simulation in Initial Teacher Education (ITE). Some areas where simulation has become a staple of initial or ongoing education and training, i.e. in health care and military applications, are examined to provide a context. The research explores the attitudes of a group of ITE students towards the use of a recently developed simulation tool and in particular considers the question of whether they view computer simulation as a ‘third place’ between faculty based ‘theory’ elements and school based ‘practice’ elements of their training or whether they consider the simulation to be enhanced ‘theory’ learning.